2005
DOI: 10.1111/j.1540-8167.2005.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Long‐Lasting Persistent Atrial Fibrillation: Clinical Outcome and Mechanisms of Subsequent Arrhythmias

Abstract: Catheter ablation of long-lasting persistent AF associated with acute AF termination achieves medium to long-term restoration and maintenance of sinus rhythm in 95% of patients. Arrhythmia recurrence in the majority of patients is AT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
517
2
17

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 682 publications
(547 citation statements)
references
References 56 publications
11
517
2
17
Order By: Relevance
“…11,15 In our analysis, conversion of AF was not associated with a superior clinical outcome. Of note, we observed only a modest rate (about 60%) of patients in whom AF terminated during ablation, 11 although most of the studies which document a positive influence of AF termination had a higher conversion rate (66%-84%).…”
Section: Conversion Of Af and Arrhythmia Recurrencementioning
confidence: 69%
See 2 more Smart Citations
“…11,15 In our analysis, conversion of AF was not associated with a superior clinical outcome. Of note, we observed only a modest rate (about 60%) of patients in whom AF terminated during ablation, 11 although most of the studies which document a positive influence of AF termination had a higher conversion rate (66%-84%).…”
Section: Conversion Of Af and Arrhythmia Recurrencementioning
confidence: 69%
“…The difference in the type of atrial arrhythmia recurrence after stand-alone PVI versus PVI plus substrate modification is explained by the different ablation techniques. It was well described in the original article by Haïssaguerre et al 15 introducing the stepwise approach that AT was the dominant arrhythmia during follow-up, occurring in 23 of 52 patients, with AF recurring in only 2 patients. This finding was confirmed in a more recent article by the same group, 16 with 72.7% of 150 patients requiring repeat procedures (36.5% for AF and 63.5% for AT).…”
Section: Types Of Recurrent Atrial Tachyarrhythmiamentioning
confidence: 99%
See 1 more Smart Citation
“…514,515 The strategy starts by pulmonary isolation, followed by ablation of CFAE, looking for reversion to sinus rhythm or AT. If this endpoint is not achieved, additional linear lesions are deployed.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…Several studies have reported these lower success rates even with more aggressive ablation paradigms. [167][168][169] Recently, the use of extensive linear ablation aimed at organizing and subsequently eliminating chronic AF achieved slightly better results but with a limited follow-up period 168,169 ( Figure 9). …”
Section: Success Ratesmentioning
confidence: 99%